The role of morphology and coupling of gold nanoparticles in optical breakdown during picosecond pulse exposures - Davletshin, Yevgeniy R.; Kumaradas, J. Carl (Beilstein Journal of Nanotechnology, 2016)
This paper presents a theoretical study of the interaction of a 6 ps laser pulse with uncoupled and plasmon-coupled gold nanoparticles. We show how the one-dimensional assembly of particles affects the optical breakdown threshold of its surroundings. For this purpose we used a fully coupled electromagnetic, thermodynamic and plasma dynamics model for a laser pulse interaction with gold nanospheres, nanorods and assemblies, which was solved using the finite element method. The thresholds of optical breakdown for off- and on-resonance irradiated gold nanosphere monomers were compared against nanosphere dimers, trimers, and gold nanorods with the same overall size and aspect ratio. The optical breakdown thresholds had a stronger dependence on the optical near-field enhancement than on the mass or absorption cross-section of the nanostructure. These findings can be used to advance the nanoparticle-based nanoscale manipulation of matter.
Keywords: electron plasma; finite element method; optical breakdown; plasmon coupling; plasmonic nanoparticles